2021
DOI: 10.3311/ppee.15869
|View full text |Cite
|
Sign up to set email alerts
|

Coplanar Waveguide-fed UWB Slotted Antenna with Notched-band Performance

Abstract: Compact coplanar waveguide Ultra-wideband (UWB) monopole antenna with band notched characteristics is presented in this paper. The band rejection is achieved by etching a circular slot on the radiating patch. The antenna is printed on the FR4-Epoxy substrate with overall dimensions of 23.5 × 31 × 1.5 mm3. The measured results indicate that the antenna operates in the frequency range from 1.76 to 11.07 GHz and rejects the band 2.42 to 5.37 GHz with an acceptable measured input impedance over the whole operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Because of its directed pattern and balanced far-field, the recommended antenna layout can be used in UWB and ground-penetrating radar (GPR) applications [21]. An antenna based on an FR4-epoxy substrate with antenna dimensions of 23.5 × 31 × 1.5 mm 3 was reported in [22]. The operating frequency range of the proposed antenna is 1.76-11.07 GHz, and the frequency range of 2.42 to 5.37 GHz is rejected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of its directed pattern and balanced far-field, the recommended antenna layout can be used in UWB and ground-penetrating radar (GPR) applications [21]. An antenna based on an FR4-epoxy substrate with antenna dimensions of 23.5 × 31 × 1.5 mm 3 was reported in [22]. The operating frequency range of the proposed antenna is 1.76-11.07 GHz, and the frequency range of 2.42 to 5.37 GHz is rejected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The simulated co-polar and [12,13]. Because of the extramodes at upper frequencies, it is observed that the magnitude of the cross-polar in the two planes augments with augmenting the frequency, also this augmentation can be attributed to the excitation of higher-order mode [14]. Moreover, the magnitude of the co-polar component undergoes a feeble distortion in shape at higher frequencies owing to the reflections along the corrugations used in the ground plane and along the borders of the radiating patch; this is confirmed by the high surface current distribution at theses edges (see Fig.…”
mentioning
confidence: 94%
“…Therefore, the design and advancement of UWB antennas are crucial for enhancing the overall performance of GPR systems. [4][5][6].…”
Section: Introductionmentioning
confidence: 99%